Scintigraphic evaluation of salivary gland function in thyroid cancer patients after radioiodine remnant ablation. (2nd April 2020) - Krčálová, Eva; Horáček, Jiří; Gabalec, Filip; Žák, Pavel; Doležal, Jiří
Abstract : Radioiodine ( 131 I, RAI) has traditionally been used in thyroid cancer treatment but its benefit should be balanced against possible risks. Among them, salivary gland dysfunction has often been discussed, although the reported data have been inconsistent. The aim of our prospective study was to evaluate salivary gland function in 31 thyroidectomised patients (6 men, 25 women; median age 52 yr) before and 4–6 months after RAI remnant ablation (RRA), using activity of 3.7 GBq 131 I‐NaI. Salivary gland uptake and excretion fractions were quantitatively assessed with 99m Tc – pertechnetate salivary gland scintigraphy. Pre‐ and post‐treatment values were compared using Wilcoxon signed rank test. No statistically significant difference in the pre‐ and post‐treatment values was observed in parotid or submandibular glands uptake, or in the parotid or submandibular excretion fractions. The calculated power for minimum relevant difference of 25% with the sample size of 31 ranged between 86% and 96% for the individual variables, making our negative results reasonably reliable. The results suggest that RRA with the most commonly used activity of 3.7 GBq has no important impact on salivary gland function. Therefore, the concerns about putative salivary gland functional deterioration following RRA are probably unjustified.